The Influence of Brand Value Co-Creation, Brand Trust, and Perceived Ease of Use on Interest In Investing Through Electronic Word of Mouth: Case Study on LANDX Investors - Maqsuda, Janggih; Sopiah; Hermawan, Agus (PT. Maju Malaqbi Makkarana, 2023)
The contribution of MSMEs to the Indonesian economy is large, but this sector still has obstacles in obtaining capital. Therefore, referring to Indonesian Capital Market regulations, the government, through the OJK (Financial Services Authority), issued Regulation Number 37/POJK.04/2018 concerning Crowdfunding Services through information technology-based share offerings (Equity Crowdfunding). LandX is an organizer registered with ALUDI which already has OJK permission. The average level of funds collected by LandX for each project is up to 4 billion. The population in this study is 88,572 investors who have registered with LandX as of December 2022. The sample was taken using purposive sampling. The conclusion of this research is that Brand trust has a significant effect on investors' investment interest, Brand value co-creation engagement attitude has no significant effect on investors' interest in investing in LandX through e-WOM, Brand value co-creation engagement behavior has a significant effect on investors' investment interest in LandX through e-WOM, Perceived ease of use has a significant effect on investors' interest in investing in LandX through e-WOM and E-WOM has a significant effect on investors' interest in investing in LandX